Prigranichnoe sotrudnichestvo Kaliningradskoj oblasti RF s Litvoj i Pol'shej: prepjatstvija i vozmozhnosti [Cross-Border Cooperation between Kaliningrad Region, Lithuania and Poland: Obstacles and Possibilities] - Schielberg Silke (Балтийский регион, 2009)
This article analyses the cross-border co-operation between the Kaliningrad Region and the neighbouring Polish and Lithuanian regions. It provides, firstly, a short overview of the cross-border co-operation formation and development. The author outlines the present-day co-operation structures. Secondly, the article reviews the asymmetries that hinder the cross-border co-operation. Finally, it offers some examples of the cross-border cultural and social projects proving that the co-operation under difficult conditions can be successful. The analysis is based on the author's empirical research and interviews with regional experts.